Knowledge networks and industrial structure for regional innovation: An analysis of patents collaborations in Italy. Issue 1 (20th November 2019) - Innocenti, Niccolò; Capone, Francesco; Lazzeretti, Luciana
Abstract: The aim of the research is to investigate whether the structure of knowledge networks and the variety of the local industrial structure are important for regional innovation and if the interplay between these two forces has an additional effect on local innovativeness. The research analyses co‐patenting collaborations at firm level in the Italian provinces in three five‐year intervals in the period 2001–2016. Results show that the structure of knowledge networks and agglomeration economies of inventors boost local inventive capacity. It also highlights how these forces have an increasing impact on innovation as the variety of the area increases. Resumen: El objetivo de la investigación es investigar si la estructura de las redes de conocimiento y la variedad de la estructura industrial local son importantes para la innovación regional y si la interacción entre estas dos fuerzas tiene un efecto adicional en la capacidad de innovación local. La investigación analiza las colaboraciones de copatente a nivel de empresa en las provincias italianas en tres intervalos de cinco años en el período 2001‐2016. Los resultados muestran que la estructura de las redes de conocimiento y las economías de aglomeración de los inventores impulsan la capacidad inventiva local. También resalta cómo estas fuerzas tienen un impacto cada vez mayor en la innovación a medida que aumenta la variedad de la zona. 抄録: 本稿では、知識ネットワークの構造と地域の産業構造の多様性は、地域のイノベーションに重要であるかどうか、また、この両者の力の相互作用が地域のイノベーション活性に付加的効果をもたらすか否かを検討する。2001~2016年の3回の5年間隔で、イタリアの県の企業レベルにおける特許の共同出願のためのコラボレーションを分析する。結果から、知識ネットワークの構造と発明者の集積の経済は地域の発明能力を大きく高めることが示される。さらに、その地域の多様性が豊かになるほど、それらの力のイノベーションに対する影響力がいかに増強されるかが強調される。